2014
DOI: 10.1371/journal.pone.0092698
|View full text |Cite|
|
Sign up to set email alerts
|

Human Traumatic Brain Injury Induces Autoantibody Response against Glial Fibrillary Acidic Protein and Its Breakdown Products

Abstract: The role of systemic autoimmunity in human traumatic brain injury (TBI) and other forms of brain injuries is recognized but not well understood. In this study, a systematic investigation was performed to identify serum autoantibody responses to brain-specific proteins after TBI in humans. TBI autoantibodies showed predominant immunoreactivity against a cluster of bands from 38–50 kDa on human brain immunoblots, which were identified as GFAP and GFAP breakdown products. GFAP autoantibody levels increased by 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 65 publications
9
136
0
Order By: Relevance
“…In parallel, we recently reported a rather unexpected immunodominant autoantibody response to GFAP and its breakdown products (BDPs) in a subset of patients with severe TBI. 26 Based on our previous anti-GFAP-autoantibody study, 26 we observed that GFAP appeared to be a dominant brain-derived autoantigen after severe TBI. We hypothesized that TBI causes protease-mediated GFAP-BDP formation in injured glial cells.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…In parallel, we recently reported a rather unexpected immunodominant autoantibody response to GFAP and its breakdown products (BDPs) in a subset of patients with severe TBI. 26 Based on our previous anti-GFAP-autoantibody study, 26 we observed that GFAP appeared to be a dominant brain-derived autoantigen after severe TBI. We hypothesized that TBI causes protease-mediated GFAP-BDP formation in injured glial cells.…”
Section: Introductionmentioning
confidence: 90%
“…To detect and quantify AutoAb[GFAP] levels in biosamples, we used our previously published manifold autoantibody immunoblotting assay format 26 (see Supplementary Fig. 1 for assay set-up; see online supplementary material at ftp.liebertpub.com).…”
Section: Measurement Of Autoab[gfap]mentioning
confidence: 99%
See 3 more Smart Citations